2008
DOI: 10.1038/cdd.2008.92
|View full text |Cite
|
Sign up to set email alerts
|

Neogenin regulates neuronal survival through DAP kinase

Abstract: The repulsive guidance molecule (RGM) is a membrane-bound protein that has diverse functions in the developing central nervous system. Identification of neogenin as a receptor for RGM provided evidence of its cell death-inducing activity in the absence of RGM. Here, we show that the serine/threonine kinase death-associated protein kinase (DAPK) is involved in the signal transduction of neogenin. Neogenin interacts with DAPK and reduces DAPK autophosphorylation on Ser308 in vitro. Neogenininduced cell death is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…The RGMa receptor neogenin plays an important role in cell death regulation in the embryonic and adult CNS (Fujita et al, 2008) mediated by two proteins directly bound to neogenin and released upon RGMa binding: death-associated protein kinase (DAPK) and LIM domain only 4 (LMO4) (Schaffar et al, 2008;Goldschneider et al, 2008;Fujita et al, 2008). These two proteins influence different intracellular pathways: DAPK, on the one hand, affects cellular survival by activating the apoptotic pathway, and LMO4, on the other hand, affects the cytoskeleton and gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The RGMa receptor neogenin plays an important role in cell death regulation in the embryonic and adult CNS (Fujita et al, 2008) mediated by two proteins directly bound to neogenin and released upon RGMa binding: death-associated protein kinase (DAPK) and LIM domain only 4 (LMO4) (Schaffar et al, 2008;Goldschneider et al, 2008;Fujita et al, 2008). These two proteins influence different intracellular pathways: DAPK, on the one hand, affects cellular survival by activating the apoptotic pathway, and LMO4, on the other hand, affects the cytoskeleton and gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…For G, n ϭ 5. *, p Ͻ 0.01; **, p Ͻ 0.05. sis in some but not all of the cell types (17,18). To test the validity of this possibility, we performed the MTT assay to assess the cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, phosphorylation of the myosin light chain by DAPK leads to membrane blebbing, a hallmark of programmed cell death (Gozuacik and Kimchi, 2006). Interestingly, it was recently suggested that UNC5H2 was not the only DR to trigger apoptosis through DAPK, as neogenin was also shown to interact with DAPK and to require DAPK for apoptosis induction (Fujita et al, 2008), in the same way that DCC, UNC5H1, 2 and 3 also require lipid raft association to induce cell death . Caspase 3 activation Apoptosis Figure 5 Model of cell death induction by UNC5H2/UNC5B.…”
Section: Amplification Of Receptor Cleavagementioning
confidence: 99%